Two new species of Enarmoniini (Lepidoptera: Tortricidae) from eastern Thailand - Muadsub, Sopita; Pinkaew, Nantasak (Zootaxa, 2014)
Two new species of the tribe Enarmoniini (Tortricidae) are described from the Chanthaburi and Trat provinces of eastern Thailand: Helictophanes flava Muadsub and Pinkaew, n. sp., and Cyphophanes khitchakutensis Muadsub and Pinkaew, n. sp. Illustrations of adults and genitalia are provided.